Bandits and Liberals, Rebels and Saints : Latin America since Independence - Knight, Alan, 1946- (Book collections on Project MUSE., 2022)
""Bandits and Liberals, Rebels and Saints" looks at nineteenth- and twentieth-century Latin American history, covering several major themes, such as banditry, liberalism, nationalism, revolutions, religion, and violence"--